Effects of physical activity, motivation, and snacking on elementary students’ physical fitness - Ifra Manto Fani; Wilda Welis; Nuridin Widya Pranoto; Ahmad Chaeroni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study aims to examine the direct and indirect effects of physical activity and snack consumption patterns on physical fitness, with exercise motivation as a mediating variable among elementary school students. A quantitative design with path analysis was applied to a sample of 65 fifth-grade students selected through random sampling. Data were collected using the Physical Activity Questionnaire for Older Children (PAQ-C), a Likert-scale motivation questionnaire, a Food Frequency Questionnaire (FFQ), and the Indonesian Physical Fitness Test (TKSI). The results showed that all independent variables significantly influenced physical fitness (p < 0.001), with exercise motivation emerging as the strongest predictor (β = 0.581; 33.75%). Physical activity (β = 0.281) and snack consumption (β = 0.311) also had significant direct effects. Moreover, both variables demonstrated indirect effects through motivation, confirmed by Sobel test results (p < 0.001). The model explained 95.2% of the variance in physical fitness. In conclusion, exercise motivation plays a critical mediating role, highlighting the importance of integrating behavioral and psychological approaches to improve students’ physical fitness